Pelatihan Pengenalan Mesin-Mesin Listrik bagi Masyarakat Seputaran Kampus USK - Rakhmad Syafutra Lubis; Ramdhan Halid Siregar; Syukriyadin Syukriyadin; Alfisyahrin Alfisyahrin; Saifuddin Muhammad Jalil (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Electrical power is used not only for lighting but also for devices that can facilitate daily activities, such as washing machines, where this device drives a device called an electric motor. Electric machines are widely used in various places to help humans complete their work. Electric machines have many types and uses according to their type. The use of an electric machine is generally very frequent, therefore the possibility of damage due to age and condition is the main cause. To extend the life of an electric machine, maintenance is necessary, and if damage occurs, it can usually be repaired so that the cost of use is cheaper when compared to buying a new electric machine as a replacement. The most common damage is in the windings of the electric machine. The windings are long conductor wires wrapped around the stator (the stationary part). This winding is where the rotating electric field will be generated which will affect the conductors in the rotor (the rotating part) so that it can rotate. This winding is the most important part of an electric machine or motor. When the electricity supply is disrupted, some people use a temporary power generator called a generator set (a generator that is driven by a combustion engine or what is called a genset). These two devices, motors and generators, are known as electrical machines. Therefore, the community service team felt the need to conduct training for several interested community members. This training, called Introduction to Electrical Machines, was conducted. By utilizing the skilled workforce already available within the Electrical and Computer Engineering Department, Faculty of Engineering, Unsyiah, including lecturers, students, and the laboratory, the training is expected to increase the number of skilled personnel in electrical machine maintenance and repair. This will, in turn, increase budget savings in the use of electric motors within the community.